2006
DOI: 10.1128/jb.01035-06
|View full text |Cite
|
Sign up to set email alerts
|

Mesorhizobium lotiProducesnodPQ-Dependent Sulfated Cell Surface Polysaccharides

Abstract: Leguminous plants and bacteria from the family Rhizobiaceae form a symbiotic relationship, which culminates in novel plant structures called root nodules. The indeterminate symbiosis that forms between Sinorhizobium meliloti and alfalfa requires biosynthesis of Nod factor, a ␤-1,4-linked lipochitooligosaccharide that contains an essential 6-O-sulfate modification. S. meliloti also produces sulfated cell surface polysaccharides, such as lipopolysaccharide (LPS). The physiological function of sulfated cell surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…The nodPQ genes (mlr7575 and mlr7576) are required for the biosynthesis of 3'-phosphoadenosine-5'-phosphosulfate, which is used for the sulfation of cellsurface polysaccharides, but not of Nod factor, in M. loti. The mutant in nodPQ elicited effective nodules with reduced nodulation kinetics (43). In addition, we confirmed that strain 06T02h06 (mutant in msl0067) was a purine auxotroph and strain 10T01g06 (mutant in mll5681) was a pyrimidine auxotroph (data not shown).…”
Section: Mutants Showing Reduced Competitiveness During Nodulationsupporting
confidence: 68%
“…The nodPQ genes (mlr7575 and mlr7576) are required for the biosynthesis of 3'-phosphoadenosine-5'-phosphosulfate, which is used for the sulfation of cellsurface polysaccharides, but not of Nod factor, in M. loti. The mutant in nodPQ elicited effective nodules with reduced nodulation kinetics (43). In addition, we confirmed that strain 06T02h06 (mutant in msl0067) was a purine auxotroph and strain 10T01g06 (mutant in mll5681) was a pyrimidine auxotroph (data not shown).…”
Section: Mutants Showing Reduced Competitiveness During Nodulationsupporting
confidence: 68%
“…PAPS was analyzed as described previously (4), as modified by Townsend et al (62). Briefly, wild-type strains harboring vector control, multicopy syrA, or multicopy nodPQ, were cultured in 1 ml of TY medium with Na 2 35 SO 4 to saturation.…”
Section: Methodsmentioning
confidence: 99%
“…Al-though common in mammalian cells, sulfated carbohydrates appear to be rare in bacteria, having only been reported in S. meliloti (9), Mycobacterium (45,55), Mesorhizobium loti (62), and Pseudoalteromonas (56) to date. The physiological function of these sulfated molecules remains obscure, although mutants of S. meliloti and M. loti with decreased polysaccharide sulfation exhibit alterations in symbiosis (11,62; D. H. Keating, G. R. O. Campbell, and G. C. Walker, submitted for publication). A recent publication reported the identification of a gene, lpsS, which encodes an LPS sulfotransferase activity in S. meliloti (11).…”
mentioning
confidence: 99%
“…The method we employed for polysaccharide preparation involved the treatment of the cells with EDTA-TEA, which is expected primarily to extract macromolecules present in the outer membrane (39,61,73). We therefore utilized an alternative method, phenol-water extraction (71), to isolate total radiolabeled cellular polysaccharides, which then were fractionated on Tris-Tricine SDS-PAGE and visualized using phosphorimaging (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The fractions obtained from size-exclusion chromatography were dialyzed to remove detergent (57) and then lyophilized. Aliquots (100 to 200 g) were subjected to glycosyl composition analysis by preparing the trimethylsilyl methyl glycoside derivatives (70), and gas chromatography-mass spectrometry was performed as described previously (71).…”
Section: Methodsmentioning
confidence: 99%